Comparative genomics of Acinetobacter baumannii from Egyptian healthcare settings reveals high-risk clones and resistance gene mobilization - Salma Salem; Dina Osama; Nehal Adel Abdelsalam; Ahmed H. Shata; Shaimaa F. Mouftah; Mohamed Elhadidy (BMC Infectious Diseases)
Abstract Background Acinetobacter baumannii (A. baumannii) has emerged as a major public health threat in low- and middle-income countries (LMICs), particularly in Egypt, due to its remarkable ability to acquire and transfer resistance genes, as highlighted in the WHO bacterial Priority Pathogens List 2024 classification. This pilot study aimed to characterize 18 A. baumannii isolates from Egyptian healthcare settings, focusing on clonal lineages, antibiotic resistance determinants, horizontal gene transfer potential, and the presence of virulence factors and chromosomal mutations. Methods Antimicrobial susceptibility testing was performed to determine resistance profiles using minimum inhibitory concentrations. Whole-genome sequencing was used to identify β-lactamase, carbapenemase, and other antibiotic resistance genes (ARGs), as well as mobile genetic elements (MGEs). Clonal relationships among isolates were assessed via core genome multilocus sequence typing (cgMLST). Results Phenotypic analysis revealed that 72% of the isolates were extensively drug-resistant (XDR), exhibiting resistance to all tested antibiotics except colistin. Clonal diversity analysis identified 11 Oxford sequence types (STs), including two novel STs (ST3309OXF and ST3321OXF), and six international clonal (IC) groups, with IC2 being the most prevalent. Additionally, eight Pasteur STs were detected, with ST570PAS being the most frequent. The cgMLST analysis showed that two Egyptian ST570PAS isolates clustered with a strain from Saudi Arabia, suggesting potential regional transmission. Genomic analysis revealed the widespread dissemination of ARGs via MGEs, particularly rep plasmids and insertion sequence elements, which contributed significantly to genomic diversity and antibiotic resistance. Conclusions This pilot study highlights the clonal diversity of A. baumannii in Egypt and underscores the critical role of MGEs in the spread of resistance genes. Targeted genomic surveillance and infection control are essential to curb the spread of high-risk resistant A. baumannii clones in Egyptian clinical settings.